BOUNDLESS COLLABORATION OF VIRTUAL MUSIC IN THE DIGITAL AGE - Holong, Kenan Bagas; Putra, I Pt. Lukita Wiweka Nugraha (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Virtual Music's Boundless Collaboration in the Digital Age Collaboration in Music has grown rapidly along with the advancement of digital technology, creating a new boundless space for musicians from different parts of the world. “Collaboration Without Borders: Virtual Music in the Digital Age” examines how digital platforms, music production software, and streaming technologies enable musical collaboration across geographies, cultures, and genres. Through the use of virtual musical instruments, remote recording, and cloud-based applications, musicians can now collaborate in real time by combining different sonic elements to produce more innovative and experimental works. In addition, this study also explores the impact of virtual collaboration on the music industry, including increased accessibility, utilization of global market potential, and challenges faced in terms of copyright and distribution. Virtual music collaboration provides musicians with an opportunity to express themselves more freely, share creative ideas, and access global opportunities without being hindered by physical boundaries.